2019
DOI: 10.1101/692335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the relationship between prenatal depression, amygdala-prefrontal structural connectivity and behaviour in preschool children

Abstract: Prenatal depression is a common, underrecognized, and undertreated condition with negative consequences on child behaviour and brain development. Neurological dysfunction of the amygdala, cingulate cortex and hippocampus are associated with the development of depression and stress disorders in youth and adults. Although prenatal depression is associated with both child behaviour and neurological dysfunction, the relationship between these variables remains unclear. In this study, fiftyfour mothers completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…This may make them more susceptible to the negative effects of PMDS, leading to an increased likelihood of neurodevelopmental disorders. For instance, studies have found that boys who were exposed to high levels of PMDS during infancy displayed symptoms such as heightened anxiety, poorer motor skills and increased sleep disturbances (Gerardin et al, 2011; Hay et al, 2019). Whether girls or boys are more vulnerable to PMDS depends on the type, severity, timing of PMDS exposures and age of the offspring at the time of investigation (Bale et al, 2015; Glover et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This may make them more susceptible to the negative effects of PMDS, leading to an increased likelihood of neurodevelopmental disorders. For instance, studies have found that boys who were exposed to high levels of PMDS during infancy displayed symptoms such as heightened anxiety, poorer motor skills and increased sleep disturbances (Gerardin et al, 2011; Hay et al, 2019). Whether girls or boys are more vulnerable to PMDS depends on the type, severity, timing of PMDS exposures and age of the offspring at the time of investigation (Bale et al, 2015; Glover et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have found, associations of frontal functional connectivity with internalizing and externalizing behavior at 24 months following PDE(Soe et al 2016). In turn, altered structural connectivity in prefrontal-limbic pathways mediated externalizing behavior following PDE in 2-6-year-old children(Hay et al 2020). The CBCL may not be a reliable measure in our setting or at this very young age when parent reports of behavior challenges tend to be less stable.The pattern in this cohort of widespread associations of PDE with decreased white matter integrity is notable.…”
mentioning
confidence: 90%
“…Diffusion tensor imaging (DTI) studies in infants with PDE have reported differences in white matter microstructural integrity of frontal and limbic regions compared to unexposed control infants (Dean et al 2018;Graham et al 2020;Rifkin-Graboi et al 2013), although not all data are consistent (Jha et al 2016). In older children (spanning 2-10 years) differences in white matter integrity have been observed in frontal, temporal and limbic regions (El Marroun et al 2018;Hay et al 2020;Lebel et al 2016). Further, altered white matter integrity of frontal-limbic networks in toddlers with PDE has been shown to predict internalizing and externalizing behaviors (Hay et al 2020;Wee et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, not all offspring are affected by prenatal stress (PNS), and intrinsic factors such as genetic or molecular factors can also play a critical role in determining the functional outcomes (Abbott et al, 2018). More in detail, long-lasting changes in brain regions, such as the amygdala (AMY), prefrontal cortex (PFC), and hippocampus can occur during key gestational periods and are reported in humans (Hay et al, 2019). These regions, especially the PFC and AMY, are strongly interconnected; and their work in concert is essential to regulate mood, emotions, and stress responsiveness (Murray et al, 2011;Likhtik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%